2011
DOI: 10.1038/srep00076
|View full text |Cite
|
Sign up to set email alerts
|

Differential Macrophage Polarization Promotes Tissue Remodeling and Repair in a Model of Ischemic Retinopathy

Abstract: Diabetic retinopathy is the leading cause of visual loss in individuals under the age of 55. Umbilical cord blood (UCB)–derived myeloid progenitor cells have been shown to decrease neuronal damage associated with ischemia in the central nervous system. In this study we show that UCB-derived CD14+ progenitor cells provide rescue effects in a mouse model of ischemic retinopathy by promoting physiological angiogenesis and reducing associated inflammation. We use confocal microscopy to trace the fate of injected h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
59
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(67 citation statements)
references
References 47 publications
3
59
0
1
Order By: Relevance
“…In addition, RAGE-null mice display improved nerve regeneration in a model of diabetic neuropathy because of enhanced M2 trans-differentiation (27). On the contrary, Marchetti et al have shown that selective M2 polarization promotes tissue repair in ischemic retinopathy (30). Therefore, a strong case can be made for the SR-A-RAGE interplay in determining macrophage function and the progression of DR.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, RAGE-null mice display improved nerve regeneration in a model of diabetic neuropathy because of enhanced M2 trans-differentiation (27). On the contrary, Marchetti et al have shown that selective M2 polarization promotes tissue repair in ischemic retinopathy (30). Therefore, a strong case can be made for the SR-A-RAGE interplay in determining macrophage function and the progression of DR.…”
Section: Discussionmentioning
confidence: 99%
“…The CD14 þ fraction, like CD34 þ cells, can respond to microenvironmental cues, regulate inflammatory cascades, respond to hypoxia, and influence the behavior of CD34 þ cells. 42 Marchetti et al 24 demonstrated that during the hyperoxic phase of the oxygen-induced retinopathy model, CD14 þ cells induce angiogenesis, reducing the area of vaso-obliteration and associated tissue hypoxia. In that study, vascular regression, associated with endothelial cell death, was avoided by CD14 þ cell-induced up-regulation of anti-apoptotic and anti-oxidative genes and associated maintenance of retinal vasculature.…”
Section: Discussionmentioning
confidence: 99%
“…CD14 þ cells polarized to M2 macrophages following injection into the eyes of mice undergoing oxygen-induced retinopathy and exerted a profound rescue effect to reduce pathological neovascularization. 24 Monocytes can also act as ''bridge cells'' when recruited from the circulation to establish tip-cell anastomosis and release of angiogenic factors to promote vessel fusion and vascular network formation. 25 Preclinical studies have investigated the use of bone marrow stem/progenitor cells to treat diabetes mellitus, genetic kidney disease, strokes, spinal cord injury, and hepatic cirrhosis.…”
Section: Conclusion Diabetic Cd14mentioning
confidence: 99%
“…в трансгенной модели болезни Альцгеймера показали, что ма-крофаги костномозгового происхождения уча-ствуют в элиминации амилоидных бляшек, обла-дая, таким образом, способностью ограничивать прогрессию когнитивных расстройств [76]. По-зитивная роль М2-макрофагов продемонстри-рована также в модели ишемической ретинопа-тии [42,50].…”
Section: Chernykh Er Et Al черных ер и др Medical Immunology (Runclassified